Words for our sponsors - Gomes, Fabio (World Nutrition, 2013)
Fabio Gomes on the links between the nutrition profession and Big Food Above: seven participants at ICN Granada who did not speak at any industry-sponsored session: Stuart Gillespie, Wilma Freire, Chessa Lutter, Andrew Collins, Claus Leitzman, Carlos Monteiro, and Harriet Kuhnlein